Using biodiversity databases to assess vascular plant diversity in Protected Areas: a case study of Parque Estadual do Forno Grande, Brazil. - Bochorny, Thuane (2024)
The Parque Estadual do Forno Grande is a fully protected area in the southern Espírito Santo State, Brazil. It belongs to the Atlantic Forest domain, with predominantly dense, ombrophilous, seasonal semi-deciduous forests and herbaceous/shrubby vegetation on rock outcrops. The area is recognised as highly important for conservation, designated as a priority biological area for protecting the Atlantic Forest's biodiversity. Although the importance of Protected Areas in conserving the Atlantic Forest biodiversity is unquestionable, it is crucial to understand the floristic patterns within these regions to develop effective conservation strategies. We utilised national online databases to compile species lists containing relevant information about their biodiversity. The updated list of vascular plants recorded in the Parque Estadual do Forno Grande is available in the “Catálogo de Plantas das Unidades de Conservação do Brasil” and it is presented here with further information on richness, endemism and conservation status.